Korelasi antara Kadar Vitamin C Plasma dengan Tekanan Darah pada Lansia di Jakarta Timur - Purnamasari, Yuti; Andayani, Diyah Eka; Hardiany, Novi Silvia (Universitas Pahlawan Tuanku Tambusai, 2024)
Introduction: The elderly population in developing countries is increasing every year.. In the elderly with increasing age, physiological functions decrease due to degenerative processes, therefore many non- communicable diseases appear in old age. Blood pressure is a parameter used to assess cardiovascular health, which is influenced by oxidative stress. Vitamin C is a strong antioxidant to reduce oxidative stress and maintain endothelial function by producing nitirc oxide. The aim of this study was to analyze the correlation between plasma vitamin C levels and blood pressure in the elderly in East Jakarta.Methods: This study used a Cross-sectional method conducted on 60 elderly members both females and males age > 60 years old in Panti Sosial Tresna Werdha Budi Mulia 1. Vitamin C intake was assessed by semi quantitative food frequency questionnaire, blood pressure was measured by sphygmomanometer and plasma vitamin C levels were detected by spectrophotometer. Analysis correlation between plasma vitamin C level and blood pressure was performed using Spearmen test. Result: This research shows that systolic blood pressure is 125 (90-160) mmHg and diastolic blood pressure is 80 (60-110) mmHg. Median Vitamin C content 0,44 (0,08- 1,81). Results bivariate analysis between plasma vitamin C levels and systolic blood pressure. obtained P>0.05. Conclusion: There was no correlation between plasma vitamin C levels and systolic and diastolic blood pressure.